Early Stepdown From Echinocandin to Fluconazole Treatment in Candidemia: A Post Hoc Analysis of Three Cohort Studies. (16th May 2021) - Moreno-García, E; Puerta-Alcalde, P; Gariup, G; Fernández-Ruiz, M; López Cortés, L E; Cuervo, G; Salavert, M; Merino, P; Machado, M; Guinea, J; García-Rodríguez, J; Garnacho-Montero, J; et al.
Abstract: Background: There are no clear criteria for antifungal de-escalation after initial empirical treatments. We hypothesized that early de-escalation (ED) (within 5 days) to fluconazole is safe in fluconazole-susceptible candidemia with controlled source of infection. Methods: This is a multicenter post hoc study that included consecutive patients from 3 prospective candidemia cohorts (2007–2016). The impact of ED and factors associated with mortality were assessed. Results: Of 1023 candidemia episodes, 235 met inclusion criteria. Of these, 54 (23%) were classified as the ED group and 181 (77%) were classified as the non-ED group. ED was more common in catheter-related candidemia (51.9% vs 31.5%; P = .006) and episodes caused by Candida parapsilosis, yet it was less frequent in patients in the intensive care unit (24.1% vs 39.2%; P = .043), infections caused by Nakaseomyces glabrata (0% vs 9.9%; P = .016), and candidemia from an unknown source (24.1% vs 47%; P = .003). In the ED and non-ED groups, 30-day mortality was 11.1% and 29.8% ( P = .006), respectively. Chronic obstructive pulmonary disease (odds ratio [OR], 3.97; 95% confidence interval [CI], 1.48–10.61), Pitt score > 2 (OR, 4.39; 95% CI, 1.94–9.20), unknown source of candidemia (OR, 2.59; 95% CI, 1.14–5.86), candidemia caused by Candida albicans (OR, 3.92; 95% CI, 1.48–10.61), and prior surgery (OR, 0.29; 95% CI, 0.08–0.97) were independent predictors of mortality. Similar results were found when a propensity score for receiving ED was incorporated into the model. ED had no significant impact on mortality (OR, 0.50; 95% CI, 0.16–1.53). Conclusions: Early de-escalation is a safe strategy in patients with candidemia caused by fluconazole-susceptible strains with controlled source of bloodstream infection and hemodynamic stability. These results are important to apply antifungal stewardship strategies. Abstract : Early de-escalation (within 5 days of candidemia onset) was proven to be safe in episodes caused by fluconazole-susceptible strains with a controlled source of candidemia and hemodynamic stability. These results might help strengthen antifungal stewardship strategies.